2000
DOI: 10.1038/77528
|View full text |Cite
|
Sign up to set email alerts
|

Minocycline inhibits caspase-1 and caspase-3 expression and delays mortality in a transgenic mouse model of Huntington disease

Abstract: Huntington disease is an autosomal dominant neurodegenerative disease with no effective treatment. Minocycline is a tetracycline derivative with proven safety. After ischemia, minocycline inhibits caspase-1 and inducible nitric oxide synthetase upregulation, and reduces infarction. As caspase-1 and nitric oxide seem to play a role in Huntington disease, we evaluated the therapeutic efficacy of minocycline in the R6/2 mouse model of Huntington disease. We report that minocycline delays disease progression, inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
527
2
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 788 publications
(553 citation statements)
references
References 30 publications
22
527
2
2
Order By: Relevance
“…As reported, minocycline also possesses potent anti-apoptotic properties. It inhibits caspase 1 and 3 expressions and directly blocks cytochrome c release from mitochondria [10,33]. Recent studies have shown that anti-inflammatory and immunomodulatory actions of minocycline are not related to its antimicrobial property [34].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As reported, minocycline also possesses potent anti-apoptotic properties. It inhibits caspase 1 and 3 expressions and directly blocks cytochrome c release from mitochondria [10,33]. Recent studies have shown that anti-inflammatory and immunomodulatory actions of minocycline are not related to its antimicrobial property [34].…”
Section: Discussionmentioning
confidence: 99%
“…Minocycline is a semi-synthetic second-generation tetracycline with anti-apoptotic, immunosuppressive and anti-inflammatory actions in various pathological states including acne vulgaris, periodontitis, rheumatoid arthritis, asthma, scleroderma, Parkinson's disease and Huntington's disease [7][8][9][10]. Underlying mechanisms of minocycline's anti-inflammatory actions which are independent from its main clinical use as an antimicrobial, include the inhibition of ROS, and cytokine production, interference with protein synthesis and modulation of matrix metalloproteinase activity [11,12].…”
Section: Objectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…, which affect the calcium homeostatic mechanism [139] and lead to deleterious consequences. Imbalance in the calcium homeostasis has been previously reported in different HD mice [140][141][142] that it is in agreement with consistent changes in the expression levels of many Ca 2+ signaling proteins [143].…”
Section: Cycle Of Neurotoxicitymentioning
confidence: 99%
“…Previous studies have revealed that minocycline successfully reduced brain damage and inflammation, protected against neurogenerative diseases, and improved cognitive functioning. 12,90 As a second alternative to minocycline, it can be argued that HTS had a positive effect on the brain as it mitigated further deterioration of injury. Finally, in comparison to other drug treatments, it is clear that notable differences exist with morphine and mannitol, as both drugs failed to recover hemodynamic parameters.…”
Section: Introductionmentioning
confidence: 99%